Project-based learning and its contribution in virtual education - Guerrero, Jacqueline Aracely Arteaga; Moreira, José Atilio Murillo; Zambrano, María José Zambrano; Rivas, Fernando Eduardo Cornejo; Pilligua, Marilyn Lidia Basurto (International research journal of management, IT and social sciences, 2021)
At the present time, teaching is going through an experience at a global level, due to the Covid 19 pandemic. Students experienced a new way of learning, because of the health emergency; In this period, project-based learning was introduced as a contribution to virtual education, a methodology that was applied in the Sebastián Muñoz Educational Unit of the San Sebastián Parish of the Pichincha canton. The purpose of this work is to carry out an analysis of the contribution that this methodological strategy has had on high school students. The criterion that is intended to show is the marked acceptance that this significant learning has had, through a detailed analysis, starting from the management of the ordinary use platform Microsoft teams with which there is direct communication in the educational community. The qualitative method is proposed based on interpreting the data obtained from the objective set, using a direct survey of students and teachers. It was obtained as a result that the schoolchildren who make use of technological tools are precisely those who have efficient connectivity and that the educators who work the most applying the studied methodology are those who adequately handle the technological elements.